2007
DOI: 10.1021/ef070197h
|View full text |Cite
|
Sign up to set email alerts
|

Scaled-Up Ocean Injection of CO2–Hydrate Composite Particles

Abstract: A pilot-scale, three-phase continuous-jet hydrate reactor, developed to produce CO2 hydrate for ocean sequestration, was tested both in the laboratory and at sea. A 72-L pressure vessel was used for laboratory tests; field experiments were performed with a remotely operated vehicle at depths between 1200 and 2000 m off the coast of Monterey, CA. Rapid production of a consolidated sinking CO2–hydrate composite paste was achieved in both settings. The vertical and lateral movement of the extruded hydrate was mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
0
29
1
1
Order By: Relevance
“…During the past 15 years the emphasis has been on natural gas storage and transportation (Gudmundsson et al, 2000;Matsuda et al, 2006;Thomas and Dawe, 2003) and on carbon dioxide capture from flue and fuel gases (Aaron and Tsouris, 2005;Kang and Lee, 2000;Klara and Srivastava, 2002;Linga et al, 2007a;Seo et al, 2005). Hydrate formation is also a factor when considering injection of CO 2 into the ocean (Lee et al, 2003;Tsouris et al, 2004Tsouris et al, , 2007. If hydrate is to be formed from liquid water then the efficient contacting of the gas with water plays a key role in the above applications.…”
Section: Introductionmentioning
confidence: 99%
“…During the past 15 years the emphasis has been on natural gas storage and transportation (Gudmundsson et al, 2000;Matsuda et al, 2006;Thomas and Dawe, 2003) and on carbon dioxide capture from flue and fuel gases (Aaron and Tsouris, 2005;Kang and Lee, 2000;Klara and Srivastava, 2002;Linga et al, 2007a;Seo et al, 2005). Hydrate formation is also a factor when considering injection of CO 2 into the ocean (Lee et al, 2003;Tsouris et al, 2004Tsouris et al, , 2007. If hydrate is to be formed from liquid water then the efficient contacting of the gas with water plays a key role in the above applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, other arrangements such as bubbles dispersed in water or water droplets injected into a gas atmosphere have been proposed (Gudmundsson et al, 2000;McCallum et al, 2007;Ohmura et al, 2002;Tsuji et al, 2004). Tsouris and co-workers have presented novel and efficient crystallizers in the context of CO 2 sequestration work (Lee et al, 2003;Tsouris et al, 2004Tsouris et al, , 2007West et al, 2001). In addition, it has also been reported that when hydrate is formed from ice, temperature ramping enhances the conversion (Susilo et al, 2007b;Wang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These data revealed that the dissolution rate of the liquid CO 2 droplet was 3.0 µmol cm -2 s -1 , with the rise rate proportional to droplet size. In later work (Tsouris et al, 2004(Tsouris et al, , 2007, we showed that a sinking slug of CO 2 hydrate could indeed be formed in the water column (Figure 4b, but only via a carefully designed injector that forced liquid CO 2 and water together in a jetted reaction tube. Yet, these solid phases too quickly dissolved on sinking into the undersaturated ocean water column, as was also shown by direct observation of the dissolution of carefully synthesized solid pellets of both CH 4 and CO 2 hydrates emplaced on the seafloor (Rehder et al, 2004).…”
Section: Experiments In the Ocean Water Columnmentioning
confidence: 92%